Przeksztalć iloczyn na sume a]3[y+6] b]7[k+4] c] 2[m-3] d] 4[a-6] e] -3[a+2] f] -2[n+3] g] -6[x-6] h] -10[x-4] i] -x[a+3] j] -2a[k+5] k] 4x[x+3] l]3x[x-5]



Odpowiedź :

Obliczenia :

[tex]3(y+6)=3\cdot y+3\cdot6=3y+18\\\\7(k+4)=7\cdot k+7\cdot4=7k+28\\\\2(m-3)=2\cdot m-2\cdot3=2m-6\\\\4(a-6)=4\cdot a-4\cdot6=4a-24\\\\-3(a+2)=-3\cdot a-3\cdot2=-3a-6\\\\-2(n+3)=-2\cdot n-2\cdot3=-2n-6\\\\-6(x-6)=-6\cdot x-6\cdot(-6)=-6x+36\\\\-10(x-4)=-10\cdot x-10\cdot(-4)=-10x+40\\\\-x(a+3)=-x\cdot a-x\cdot3=-ax-3x\\\\-2a(k+5)=-2a\cdot k-2a\cdot5=-2ak-10a\\\\4x(x+3)=4x\cdot x+4x\cdot3=4x^2+12x\\\\3x(x-5)=3x\cdot x-3x\cdot5=3x^2-15x[/tex]

a]3[y+6]=3y+18

b]7[k+4] =7k+28

c] 2[m-3] =2m+(-6)

d] 4[a-6] =4a+(-24)

e] -3[a+2]= -3a+(-6)

f] -2[n+3] = -2n+(-6)

g] -6[x-6]= -6x+36

h] -10[x-4]= -10x+40

i] -x[a+3]= -xa+(-3)

j] -2a[k+5]=-2ak+(-10a)

k] 4x[x+3]=4x²+12x

l]3x[x-5]=3x²+(-15x)

Chodzi o sumy, czyli dodawanie, więc nie moze byc 2m-6.trzeba wpisac 2m+(-6) mimoze to samo wyjdzie XD